The discipline genre and the didactic transposition of learning contents and the foreign language - Alberteris Galbán, Orlando; Estrada Aguilera, Pablo; Cañizares Hinojosa, Viviana (Transformación, 2024)
Objective: The discipline genre related problems faced by the students at the university reveal the need of figuring out the corresponding ways of inclusion in the new and complex academic culture. This article aims at examining the characteristic features of the discipline genre and the implications of its didactic transposition in learning contents and the foreign language. Methods: The didactic transposition theoretical framework construction was needed for determining, through the analysis and synthesis, the necessary elements to devise the didactic approach of mathematical contents related to discipline genres teaching and learning. Results: The main finding of the paper involved the description and foundations of the generic perspective and the implications of its didactic transposition in the field of learning contents and the foreign language. The paper also includes a full description of an assessment tool of a generic progressive character, focused on the learning of mathematics contents through oral interaction, reading comprehension and academic writing in the foreign language. These tasks include the recognition of mathematics objects from written sources (in English) and its representation in several semiotic systems, its corresponding comprehension, communication and translation to mathematics codes. Conclusions: The basic elements of generic perspective have contributed to install planning, organization and evaluation of disciplinary contents and linguistic-communicative aspects in accordance with socio-cultural factors in teaching and learning a unit, widening the potentials of the English Language Curricular Strategy based fostering the didactic transposition of contents and the foreign language.